2021
DOI: 10.3390/molecules26030706
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Signalling Pathways That Link Apoptosis and Autophagy to Cell Death Induced by Estrone Analogues Which Reversibly Depolymerize Microtubules

Abstract: The search for novel anti-cancer compounds which can circumvent chemotherapeutic drug resistance and limit systemic toxicity remains a priority. 2-Ethyl-3-O-sulphamoyl-estra-1,3,5(10)15-tetraene-3-ol-17one (ESE-15-one) and 2-ethyl-3-O-sulphamoyl-estra-1,3,5(10)16-tetraene (ESE-16) are sulphamoylated 2-methoxyestradiol (2-ME) analogues designed by our research team. Although their cytotoxicity has been demonstrated in vitro, the temporal and mechanistic responses of the initiated intracellular events are yet to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…The decreased cell killing effect, observed when autophagosome formation was inhibited by 3MA, demonstrated that blockage of autophagosome traffic and the accumulation of autophagosomes promotes paclitaxel-induced cancer cell death [144]. In line with these findings, several new tubulin binding agents have been shown to activate apoptosis as a result of autophagic flux inhibition in cancer cells [145][146][147][148]. It could be envisaged that induction of autophagosome formation in response to prolonged mitotic arrest and/or mitotic slippage, together with the reduction of autophagosome turnover by flux blockage, could result in the accumulation of autophagosomes, the intracellular persistence of toxic substances and/or damaged organelles, the production of oxygen reactive species, and cytotoxicity [149].…”
Section: Autophagy-microtubule Crosstalk As a Possible Target For Cancer Growth Controlmentioning
confidence: 77%
“…The decreased cell killing effect, observed when autophagosome formation was inhibited by 3MA, demonstrated that blockage of autophagosome traffic and the accumulation of autophagosomes promotes paclitaxel-induced cancer cell death [144]. In line with these findings, several new tubulin binding agents have been shown to activate apoptosis as a result of autophagic flux inhibition in cancer cells [145][146][147][148]. It could be envisaged that induction of autophagosome formation in response to prolonged mitotic arrest and/or mitotic slippage, together with the reduction of autophagosome turnover by flux blockage, could result in the accumulation of autophagosomes, the intracellular persistence of toxic substances and/or damaged organelles, the production of oxygen reactive species, and cytotoxicity [149].…”
Section: Autophagy-microtubule Crosstalk As a Possible Target For Cancer Growth Controlmentioning
confidence: 77%
“…MTAs like taxotere, epothilone B, discodermolide, vincristine, and colchicine have been shown to inhibit HIF-1α nuclear accumulation and activity by disrupting MT function [194]. Finally, 2-methoxyestradiol (2ME2) is a natural molecule derived from the hormone estradiol that also alters MT dynamics and has antitumor and antiangiogenic properties [195][196][197]. 2ME2 impairs HIF-1α function and therefore inhibits angiogenesis [194,198].…”
Section: Antiangiogenic Effectsmentioning
confidence: 99%
“…2ME2 and its sulfamoylated analogs address those parameters and indeed have been shown to pre-sensitize prostate and breast cancer cells to radiation whilst selectively sparing non-neoplastic cells [25][26][27][28]. The nonfunctional microtubules result in a G 1 and/or a G 2 -M phase block, which are described as the most radiosensitive phases of the cell cycle [29,30]. Additionally, increased generation of reactive oxygen species (ROS) from exposure to the 2ME2/2ME2 analogs may contribute to those formed by the intracellular water-photon reaction from the radiation, resulting in intrinsic apoptosis and DNA damage.…”
Section: Introductionmentioning
confidence: 99%